375. PATTERNS OF RECURRENT DISEASE AFTER NEOADJUVANT CHEMORADIOTHERAPY AND ESOPHAGEAL CANCER SURGERY WITH CURATIVE INTENT. (24th September 2022) - Schuring, Nannet; Stam, WT; Plat, VD; Kalff, MC; Hulshof, MCCM; van Laarhoven, HWM; Derks, S; van der Peet, DL; van Berge Henegouwen, MI; Daams, F; Gisbertz, SS
Abstract: Recurrence is frequently observed in patients after esophageal cancer surgery and post-recurrence survival is dismal. Neoadjuvant chemoradiotherapy (nCRTx) followed by esophagectomy is the gold standard of care for resectable esophageal tumors in The Netherlands. This study investigated the recurrence patterns and survival in patients after nCRTx and esophagectomy. This retrospective cohort study included data from a prospectively maintained database of patients with recurrent disease after nCRTx followed by esophagectomy in the Amsterdam UMC between 01-01-2010 and 31-12-2018. Post-recurrence treatment and survival were investigated for patients specified for tumor histology (adenocarcinoma [AC] or squamous cell carcinoma [SCC]) and by recurrence site (loco-regional, distant, or combined loco-regional and distant). In total, 340 of the 803 patients included (42.3%) after nCRTx and esophagectomy developed a recurrent disease at a median of 49 and 51 weeks postoperatively, for patients with an AC or SCC, respectively. Fifty patients had loco-regional (14.7%, AC:11.2%/n = 31, SCC:32.2%/n = 19), 167 patients distant (49.1%, AC:52.3%/n = 145, SCC:33.9%/n = 20) and 122 patients had combined recurrences (35.9%, AC:36.5%/n = 101, SCC:33.9%/n = 20). Post-recurrence survival was superior for AC patients with loco-regional (33 weeks, 95%CI:7.3-58.7) compared to AC patients with distant (12 weeks, 95%CI 6.9-17.1) or combined recurrences (18 weeks, 95%CI:9.3-26.7). AC patients with loco-regional recurrences receiving curative intent treatment had the longest survival (87 weeks, 95%CI:6.9-167.4). Most esophageal cancer recurrences after curatively intended treatment were located at distant or combined loco-regional and distant sites, with limited survival prospects. A subgroup of patients with loco-regional recurrence can be treated with curative intent and has prolonged survival. How to identify these patients needs to be investigated, as they may benefit from close postoperative surveillance.